Analisis Terhadap Minat Membaca Siswa Kelas Tinggi di Sekolah Dasar - Helda Mega; Haryadi Haryadi (Journal of Elementary School (JOES), 2022)
This research has done at Sekolah Dasar Negeri 1 Pringsurat. The aims of the research are to know how is student reading interest, the efforts for improving student reading interest, to find out supported factors ad unsupported factors on students’ reading interest. The method of the research is Mix Method. The kind of the research is Survey research. The subjects and the populations of he research are high grade students (IV, V and VI) and it is consist of 60 the object of the research is students’ reading interest. The technique of the research are: indirect communication, direct communication, direct obsevation and study documentation. The instruments of collecting data are questionnaire, interview, observation and documentation. After analyzing of the thesis, the result shows that percentage students’ reading interst is 80%, furthermore, it is known that supporting factors of student’s interest of reading are student awareness display tools, methodes used, good situation and supporting environtmen. Mean while the obstacles are the teacher does not know what student’s want is, lack of facilities and the teacher does not master the methode that appropriate with student’s want, moreover to improve student’s interest of reading it needs some efforts like develop student’s happiness toward the passage so that obligation but, because reading is their hobby and give the understanding to student’s that reading is important. It can said that tudents’ reading interest at S ekolah Dasar Negeri 1 Pringsurat are good and very strong. Keywords: Students’ Reading Interest